2015
DOI: 10.4103/0976-237x.152937
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of the effect of dentin desensitizers on the retention of complete cast metal crowns

Abstract: Context:Desensitizers are used to reduce dentin hypersensitivity. They affect the surface texture of prepared dentin and may alter the retention of fixed restorations.Aims:The aim was to evaluate the effect of dentin desensitizers on the retention of complete cast metal crowns luted with glass ionomer cement.Subjects and Methods:Fifty freshly extracted human premolars were subjected to standardized tooth preparation (20° total convergence, 4 mm axial height) with a computer numerically controlled machine. Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 23 publications
3
20
0
1
Order By: Relevance
“…The current results support the first null hypothesis of the study, implying that pretreatment with Colgate Sensitive Pro-Relief Desensitizing Paste would have no effect on the retentive strength of SLM Co-Cr crown copings cemented to human extracted teeth with GIC or ZPC. Our results are in agreement with those of another study that demonstrated that pretreating dentin surfaces with Pro-Relief Desensitizing Paste prior to cementation did not affect the retention of complete cast metal crowns luted with GIC [25]. Moreover, in the aforementioned study, pretreatment with Pro-Relief showed the best retention of complete cast metal crowns compared to all other dentin desensitizers tested.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current results support the first null hypothesis of the study, implying that pretreatment with Colgate Sensitive Pro-Relief Desensitizing Paste would have no effect on the retentive strength of SLM Co-Cr crown copings cemented to human extracted teeth with GIC or ZPC. Our results are in agreement with those of another study that demonstrated that pretreating dentin surfaces with Pro-Relief Desensitizing Paste prior to cementation did not affect the retention of complete cast metal crowns luted with GIC [25]. Moreover, in the aforementioned study, pretreatment with Pro-Relief showed the best retention of complete cast metal crowns compared to all other dentin desensitizers tested.…”
Section: Discussionsupporting
confidence: 92%
“…No significant difference in the bonding strength of composites to enamel or dentin pretreated with this desensitizing paste has been reported [22][23][24]. In addition, pretreating dentin surfaces with Pro-Relief Desensitizing Paste prior to cementation did not affect the retention of complete cast metal crowns luted with a glass ionomer cement (GIC) [25] or the retention of zirconium oxide crowns luted with a resin-modified GIC or a self-adhesive resin cement [26].…”
Section: Introductionmentioning
confidence: 99%
“…Fluoride varnishes (Duraphat and Seal & Protect) provided immediate relief after application in 68-75% of sensitive teeth in patients with low dentine sensitivity. When sensitivity was intense, the therapeutic effect was on the level of [25][26][27][28][29][30][31][32][33][34][35][36].4% of teeth not responding to the applied stimuli. The therapeutic effect after 6 weeks was maintained at 66.6-70% for teeth with low sensitivity and 45.…”
Section: Wyniki Pasta Tooth Mousse Szybko Przynosiła Ulgę Natychmiasmentioning
confidence: 99%
“…30 Były wykonywane badania, w których autorzy sprawdzali wpływ wybranych metod chemicznych i fizycznych na strukturę obnażonej zębiny po opracowaniu zębów pod korony metalowe. 31 Badaniem objęto 50 ludzkich zębów, które po ekstrakcji temporary cements with pain-relieving properties, antiseptic preparations, chemical methods, physical methods, e.g. laser therapy, are used.…”
Section: Dyskusjaunclassified
See 1 more Smart Citation